The impact of disease on behavior: altering behavior in the course of disease in aging cats - Eisinger, Joana; Kuhne, Franziska; Justus Liebig University Giessen (My University, 2025)
Associations between age-related diseases and behavioral alterations have been highlighted in previous studies. This study investigates the prevalence of diseases and behavioral changes in non-diseased and diseased senior cats before and after diagnosis, concentrating on four prevalent diseases: 1. osteoarthritis, 2. chronic kidney disease, 3. hyperthyroidism, and 4. cognitive dysfunction syndrome. An online survey was performed by 594 German cat-owners with a cat older than nine years; prevalent diseases, related medications, and scaled behavioral questions before and after diagnosis were queried. Chi-Quadrat-Test and Spearman’s rank correlation were used to detect correlations between behavioral changes and diseases. Multiple linear regression was used to determine dependencies between behavioral changes and each disease pre- and post-diagnosis. Half of the cats had at least one disease diagnosed (54.6%). The most prevalent diseases were osteoarthritis (18.9%), chronic kidney disease (12.3%), and hyperthyroidism (8.9%). Cognitive dysfunction syndrome was diagnosed in 2.9% of the cats. With increasing age, the likelihood of developing at least one disease rose (rs = 0.204, p < 0.001). Disease-associated behavioral changes were found in the four mentioned diseases, with some behavioral changes occurring before diagnosis. These findings underscore the relevance of early detection of underlying diseases to decelerate ongoing behavioral changes in treatable diseases.
Keywords: ddc:630